Modern transcriptome data processing algorithms: a review of methods and results of approbation - M. V. Sprindzuk; L. P. Titov; A. P. Konchits; L. V. Mozharovskaya (Системный анализ и прикладная информатика)
Analysis of bioinformatics data is an actual problem in modern computational biology and applied mathematics. With the development of biotechnology and tools for obtaining and processing such information, unresolved issues of the development and application of new algorithms and software have emerged.Authors propose practical algorithms and methods for processing transcriptomic data for efficient results of annotation, visualization and interpretation of bioinformatics data.